2022
DOI: 10.25100/cm.v53i1.4920
|View full text |Cite
|
Sign up to set email alerts
|

Tendencias en la incidencia y la mortalidad por cáncer en Manizales, Colombia, 2008-2017

Abstract: Objetivo Describir las tendencias en incidencia y mortalidad por cáncer en Manizales, Colombia, entre 2008-2017. Métodos Se incluyeron todos los casos incidentes de cáncer en Manizales captados por el Registro Poblacional de Cáncer de Manizales entre el 1º de enero de 2008 y el 31 de diciembre de 2017, así como todas las muertes causadas por cáncer en el mismo periodo. La población en riesgo se obtuvo de las estadísticas del DANE. Se calcularon tasas de incidencia y mortalidad ajustadas por e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Few recent, large-scale estimates specifically focus on cancer incidence trends by sex across all cancer site. Many of them use less comprehensive dataset due to the limited number of tumor site (6) or time horizon (7)(8)(9) or are limited to a specific age (i.e. childhood, young adults and older adults) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Few recent, large-scale estimates specifically focus on cancer incidence trends by sex across all cancer site. Many of them use less comprehensive dataset due to the limited number of tumor site (6) or time horizon (7)(8)(9) or are limited to a specific age (i.e. childhood, young adults and older adults) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Según Globocan, en Colombia se estimaron 10.873 casos nuevos de CCR en el año 2020, para una tasa de incidencia ajustada para la edad (TIAE) de 16,9 por 100.000 habitantes; y 5417 muertes, correspondientes a una tasa de 8,2 defunciones por cada 100.000 habitantes 4 . Estudios de base poblacional en Bucaramanga 5 , Cali 6 y Manizales 7 han mostrado tendencia al aumento en la incidencia y en la mortalidad por este cáncer.…”
Section: Introductionunclassified
“…According to Globocan, 10,873 new cases of CRC were estimated in Colombia in 2020, for an age-adjusted incidence rate (AAIR) of 16.9 per 100,000 inhabitants; and 5,417 deaths, corresponding to a rate of 8.2 deaths per 100,000 inhabitants 4 . Population-based studies in Bucaramanga 5 , Cali 6 , and Manizales 7 have shown an increasing trend in the incidence and mortality from this cancer.…”
Section: Introductionmentioning
confidence: 99%